Establishing Normative Dynamic Postural Control Values in Elite Female Handball Players - Brice Picot; Jeanne Dury; Guillaume Néron; Patrick O McKeon; Nicolas Forestier (North American Sports Medicine Institute, 2022)
# Background Lower extremity injuries among young female handball players are very common. The modified Star Excursion Balance Test (mSEBT) is a valid clinical tool to assess dynamic postural control and identify athletes with higher risk of injury. However, its interpretation is difficult since performance on this test is highly sport dependent. No normative values on the mSEBT exist in handball. # Purpose The aim of this investigation was to establish normative ranges of mSEBT performance in young, healthy female handball players to help practitioners when interpreting risk estimates. # Study design Cross-Sectional Study # Methods Athletes from 14 elite teams were recruited during a national tournament and performed 3 trials in the anterior (ANT), posteromedial (PM), posterolateral (PL) directions of the mSEBT. Means, standard deviations and 95% confidence intervals (95%CI) of normalized reached distances were calculated for each direction and the composite score (COMP). Level of asymmetry between dominant and non-dominant limbs were calculated for each direction using Bland Altman analyses. Group differences were weighed against the established mSEBT minimum detectable differences (MDD) to compare scores between limbs and across different player positions. # Results One-hundred and eighty-eight females (16.8±0.9 years) were tested. Mean reach distances were 65.2±5% (64.7-65.7), 110.0±6.2% (109.3-110.6), 107.1±6.2% (106.5-107.8) and 94.1±4.9% (93.6-94.6) for the ANT, PM, PL directions and COMP score respectively. Bias and limits of agreement for limb asymmetry were -0.23% (-5.85%, 5.38%) for ANT, -0.83% (-8.80%, 7.14%) for PM, 0.33% (-8.51%, 9.17%) for PL and -0.27% (-4.88%, 4.33%) for COMP score. No meaningful differences were observed between limbs or across player positions since the values did not exceed the MDD and all 95%CIs overlapped. # Conclusion This study provides normative performance values for dynamic postural control as measured by the mSEBT among young, healthy, elite female handball players. Considering the high incidence of injury in this population, these values can be used for injury risk reduction and return to sport decisions. Further prospective studies are needed to established specific cut-off scores in this population. # Level of evidence 2c